Is child labor harmful? The impact of working earlier in life on adult earnings - Patrick M. Emerson; André Portela Souza (Institute for the Study of Labor (IZA), 2007)
This paper explores the question: is working as a child harmful to an individual in terms of adult outcomes in earnings? Though an extremely important question, little is known about the effect of child labor on adult outcomes. Estimations of an instrumental variables earnings model on data from Brazil show that child labor has a large negative impact on adult earnings for male children even when controlling for schooling and that the negative impact of starting to work as a child reverses at around ages 12-14.
Keywords: 330; Child labor; Brazil; adult outcomes; Kinderarbeit; Erwachsene; Erwerbsverlauf; Lebenseinkommen; Brasilien